Low-temperature-resistant polymer cement-based waterproof coating as well as preparation method and application thereof

By adding gelatin-sodium alginate to the polymer cement-based waterproof coating, the phase change microcapsules and sodium citrate coated with n-tetradecane, the problem of slow curing of the coating in low-temperature environment and insufficient anti-freeze-thawing ability is solved, and the efficient curing of the coating and good low-temperature resistance are achieved.

CN119823614AActive Publication Date: 2025-04-15GUANGZHOU LIGAO BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510032800.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing polymer cement-based waterproof coatings have slow curing and reduced flexibility in low-temperature construction environments, and their freeze-thaw cycle resistance is limited, making it difficult to adapt to low-temperature environments for a long time.

Method used

Ethylene-vinyl acetate copolymer emulsion and aqueous nitrile latex are used as polymers, silicate cement and magnesium phosphate cement are used as cement-based gelling materials, and gelatin-algin alginate is added to coat n-tetradecane phase-change microcapsules and sodium citrate to improve the low temperature resistance of the coating.

Benefits of technology

It significantly improves the curing speed, flexibility and anti-freeze-thawing ability of waterproof coatings at low temperatures, extends the service life of the coatings, and adapts to the construction needs of severe cold areas in the north.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005234648170000101
    Figure BDA0005234648170000101
Patent Text Reader

Abstract

The invention relates to a low-temperature-resistant polymer cement-based waterproof coating as well as a preparation method and application thereof. The coating consists of a component A and a component B, during use, the component A and the component B are mixed according to the mass ratio of 1: (0.5-2) for use; the component A is prepared from the following raw materials in parts by weight: 100 to 150 parts of ethylene-vinyl acetate copolymer emulsion, 10 to 20 parts of water-based butyronitrile latex, 2 to 5 parts of coalescing agent, 3 to 5 parts of plasticizer, 1 to 3 parts of defoaming agent and 20 to 50 parts of deionized water; the component B is prepared from the following raw materials in parts by weight: 100 to 150 parts of Portland cement, 50 to 60 parts of magnesium phosphate cement, 10 to 20 parts of gelatin-sodium alginate coated n-tetradecane phase change microcapsules and 10 to 20 parts of citric acid. The coating has the advantages of high curing speed, high low-temperature flexibility, high freeze-thaw resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer cement-based waterproof coatings, and in particular to a low-temperature-resistant polymer cement-based waterproof coating and a preparation method and application thereof. Background Art

[0002] Polymer cement-based waterproof coating, also known as JS waterproof coating, is a two-component waterproof coating with water-based polymer emulsion and cement as the main body. The two components need to be mixed evenly to a fine slurry at the construction site, and then can be brushed or sprayed on the base surface. After curing, it forms a flexible and high-strength waterproof layer. This coating combines the high strength of cement-based materials and the bonding properties of easily moist base surfaces, as well as the excellent elasticity and waterproof properties of polymer coatings. In particular, it uses a water-based system, which effectively avoids the environmental pollution that may be caused by asphalt, tar and organic solvents. It is a green, environmentally friendly, non-toxic and harmless waterproof material that is easy to construct. Since polymer cement-based waterproof coating was recommended as the preferred material, it has been widely used in many fields such as building exterior walls, roofs, kitchens, toilets, underground facilities and bridges.

[0003] However, the coating still faces challenges in practical application, especially in low-temperature construction environments. Because water-based polymer emulsions are sensitive to temperature changes and the proportion of polymer emulsions is reduced to control costs, the coating cures slowly under low-temperature conditions, its flexibility decreases, and its ability to resist freeze-thaw cycles is limited, making it difficult to adapt to low-temperature environments for a long time. This problem is particularly prominent in the cold northern regions.

[0004] In summary, current polymer cement-based waterproof coatings have obvious shortcomings in low-temperature construction performance, such as slow curing, insufficient flexibility and limited freeze-thaw resistance. Therefore, it is particularly urgent and of great significance to develop a low-temperature resistant polymer cement-based waterproof coating that can adapt to low-temperature environments. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a low-temperature resistant polymer cement-based waterproof coating and a preparation method and application thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a low-temperature resistant polymer cement-based waterproof coating, the coating comprising component A and component B; when used, component A and component B are mixed in a mass ratio of 1:(0.5-2);

[0008] Component A comprises the following raw materials in parts by weight: 100-150 parts of ethylene-vinyl acetate copolymer emulsion (EVA emulsion), 10-20 parts of water-based nitrile latex, 2-5 parts of film-forming aid, 3-5 parts of plasticizer, 1-3 parts of defoamer and 20-50 parts of deionized water;

[0009] Component B includes the following raw materials in parts by weight: 100-150 parts of silicate cement, 50-60 parts of magnesium phosphate cement, 10-20 parts of phase change microcapsules, and 10-20 parts of sodium citrate;

[0010] The wall material of the phase change microcapsule is a composite of gelatin and sodium alginate, and the core material is n-tetradecane.

[0011] N-tetradecane is a commonly used phase change material with high latent heat of phase change and suitable phase change temperature. In order to improve its stability, the present invention uses gelatin-sodium alginate as a wall material to coat n-tetradecane to form a stable microcapsule structure. This microcapsule not only retains the phase change characteristics of n-tetradecane, but also improves its stability and durability through the protective effect of the wall material. N-tetradecane (C14) can undergo phase change at about 5°C and has a high latent heat of phase change. When the ambient temperature drops below the phase change temperature, C14 will change from liquid to solid and release a large amount of latent heat. Under low temperature conditions, the free water in cement-based materials is easy to freeze and produce volume expansion, resulting in stress inside the material and possibly causing cracks, and the addition of n-tetradecane can absorb and store this part of the latent heat released due to water freezing through its phase change process, thereby slowing down or preventing the process of water freezing. In this way, C14 effectively prevents material damage caused by water freezing expansion and improves the low temperature resistance of cement.

[0012] As an effective air introduction agent, gelatin can form tiny pores in cement paste. These pores can act as buffer spaces when cement materials are subjected to freeze-thaw cycles, reducing the internal pressure caused by the expansion of water freezing, thereby reducing the formation of cracks and improving the low-temperature resistance of cement materials. Sodium alginate is a water-soluble polymer with a large number of hydroxyl and carboxyl groups in its molecular structure, which can react with Mg in magnesium phosphate cement. 2+ A cross-linking reaction occurs to form a three-dimensional network structure to fill the pores in the polymer cement-based waterproof coating, thereby improving the density of the material, thereby reducing the space for water penetration and ice expansion at low temperatures, and enhancing the low temperature resistance of the material. Therefore, the present invention selects gelatin and sodium alginate as the wall materials of the microcapsules, and the two show a significant synergistic effect in the waterproof coating, so that the waterproof coating can better resist problems such as water penetration, ice expansion and stress concentration at low temperatures, thereby significantly improving the low temperature resistance of the material.

[0013] At the same time, sodium citrate can also react with Mg in magnesium phosphate cement. 2+Chelation occurs and a new phase is formed, which makes the polymer cement-based waterproof coating have higher mechanical strength and better water resistance.

[0014] Specifically, the preparation method of the phase change microcapsule comprises the following steps:

[0015] (1) adding sodium alginate and gelatin into distilled water respectively, stirring until dissolved, to obtain a sodium alginate solution and a gelatin solution;

[0016] (2) adding n-tetradecane and an emulsifier to the gelatin solution and mixing them uniformly to obtain an emulsion;

[0017] (3) slowly adding sodium alginate solution to the emulsion, adjusting the pH to 3.0-4.0, to obtain a mixed solution;

[0018] (4) adding calcium chloride solution to the mixed solution, stirring and solidifying, standing, removing the supernatant, washing with distilled water, removing most of the solvent by vacuum rotary evaporation, filtering the precipitated solid, washing, and vacuum drying to obtain gelatin-sodium alginate coated n-tetradecane phase change microcapsules;

[0019] The mass ratio of n-tetradecane to the emulsifier is 1:(0.1-0.3), and the mass ratio of n-tetradecane, gelatin solution and sodium alginate solution is 1:(1-2):(1-2).

[0020] Preferably, the emulsifier in step (2) is Tween-80.

[0021] Preferably, in step (3), a glacial acetic acid solution with a mass concentration of 10-20% is added to adjust the pH.

[0022] Preferably, in step (4), the mass concentration of the sodium alginate solution is 70-80%, the mass concentration of the gelatin solution is 70-80%, the mass concentration of the calcium chloride solution is 70-80%, and the amount of calcium chloride solution added is 40-50wt% of the mixed solution.

[0023] Preferably, the film-forming aid is propylene glycol methyl ether acetate.

[0024] Preferably, the plasticizer is at least one of dioctyl sebacate, dioctyl adipate and dioctyl terephthalate.

[0025] Preferably, the defoaming agent is a silicone defoaming agent.

[0026] In a second aspect, the present invention provides a method for preparing the low-temperature resistant polymer cement-based waterproof coating provided in the first aspect, comprising the following steps:

[0027] S1, stirring and mixing the formulated amount of ethylene-vinyl acetate copolymer emulsion, water-based nitrile latex, film-forming aid, plasticizer, defoamer and deionized water, and filling to obtain the A component;

[0028] S2. Put the formulated amount of silicate cement, magnesium phosphate cement, phase change microcapsules and sodium citrate into a powder mixing kettle, stir and mix, and obtain the B component.

[0029] Preferably, in step S1, the stirring speed is 5000-8000 r / min and the stirring time is 2-4 h.

[0030] Preferably, in step S2, the stirring speed is 60-100 r / min and the stirring time is 4-8 h.

[0031] In a third aspect, the present invention provides use of the low-temperature resistant polymer cement-based waterproof coating described in the first aspect in the preparation of outdoor building coatings.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The polymer cement-based waterproof coating of the present invention uses ethylene-vinyl acetate copolymer emulsion (EVA emulsion) and water-based nitrile latex as polymers, uses silicate cement and magnesium phosphate cement as cement-based gelling materials, and adds gelatin-sodium alginate-coated n-tetradecane phase change microcapsules and sodium citrate. The n-tetradecane is encapsulated in the microcapsules, which not only retains the phase change characteristics of the n-tetradecane, but also improves its stability and durability through the protective effect of the wall material. The n-tetradecane, as a phase change material, can absorb and store the latent heat released by the freezing of water, thereby slowing down or preventing the water from freezing. The process of stopping water from freezing prevents material damage caused by water freezing and expansion, and improves the low-temperature resistance of cement; gelatin, as an effective air introduction agent, can form tiny pores in cement paste, which can play a buffering role in low-temperature environments, thereby improving the antifreeze performance of cement materials; sodium alginate improves the density and uniformity of the material by forming a three-dimensional network structure, and the addition of phase change microcapsules enables waterproof coatings to better resist water penetration, ice expansion and stress concentration at low temperatures, thereby significantly improving the low-temperature resistance of the material. Sodium citrate combines with Mg 2+ Chelation improves the compactness of the coating, thereby enhancing the mechanical strength and water resistance of the coating. The polymer cement-based waterproof coating of the present invention has the advantages of fast curing, good low-temperature flexibility, strong freeze-thaw resistance, etc. by adding phase change microcapsules and sodium citrate. DETAILED DESCRIPTION

[0034] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0035] The sources of materials for the following embodiments and comparative examples are as follows:

[0036] Ethylene-vinyl acetate copolymer emulsion: manufacturer is Wuhan Jiyesheng Chemical Co., Ltd., product number is A0060;

[0037] Water-based nitrile latex: The manufacturer is Dongguan Mingyuan Plastic Co., Ltd., the product number is JB15, the solid content is ≥43.5%, the pH is 7.5-9.0, the viscosity is 15-80mPa·s (normal temperature), and the acrylonitrile content is about 35% (based on the monomer component)

[0038] Propylene glycol methyl ether acetate: manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., model number is PB04652;

[0039] Dioctyl sebacate: manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., model number is PB14028;

[0040] Dioctyl adipate: manufacturer is Guangzhou Yuanda New Materials Co., Ltd.;

[0041] Dioctyl terephthalate: The manufacturer is Guangzhou Yuanda New Materials Co., Ltd.;

[0042] Gelatin: manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., model number is PA00256;

[0043] Sodium alginate: manufacturer is Shanghai Haohong Biopharmaceutical Technology Co., Ltd., model number is 1087623;

[0044] Gum Arabic: Manufacturer: Guangdong Wengjiang Chemical Reagent Co., Ltd., model number PA37901;

[0045] Chitosan: manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., model number is C105799, deacetylation degree ≥95%;

[0046] Tween-80: Manufacturer: Guangdong Wengjiang Chemical Reagent Co., Ltd., model: PB01659;

[0047] Defoamer: silicone defoamer, manufactured by Dow Chemical Company, model AFE-1410;

[0048] Portland cement: the manufacturer is Hubei Jusheng Technology Co., Ltd., the product number is JS4427;

[0049] Magnesium phosphate cement: the manufacturer is Guizhou Magnesium Phosphate Material Co., Ltd., the product numbers are material A and material B. When used in the present invention, material A and material B need to be mixed in a mass ratio of 1:1;

[0050] Sodium citrate: The manufacturer is Shanghai Haohong Biotechnology Co., Ltd., model number is 1067252, purity is 98%.

[0051] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.

[0052] Example 1

[0053] A low-temperature resistant polymer cement-based waterproof coating, the coating is composed of component A and component B; component A comprises the following raw materials in parts by weight: 125 parts of ethylene-vinyl acetate copolymer emulsion, 13 parts of water-based nitrile latex, 4 parts of film-forming aid, 4 parts of plasticizer, 2 parts of defoamer and 30 parts of deionized water;

[0054] Component B includes the following raw materials in parts by weight: 130 parts of Portland cement, 55 parts of magnesium phosphate cement, 16 parts of phase change microcapsules, and 15 parts of sodium citrate;

[0055] Wherein, the film-forming aid is propylene glycol methyl ether acetate, the plasticizer is dioctyl sebacate and dioctyl adipate in a mass ratio of 1:1, and the defoamer is an organosilicon defoamer;

[0056] The preparation method of the phase change microcapsule comprises the following steps:

[0057] (1) adding sodium alginate and gelatin into distilled water respectively, stirring until dissolved, to obtain a sodium alginate solution and a gelatin solution;

[0058] (2) adding n-tetradecane and an emulsifier to the gelatin solution and mixing them uniformly to obtain an emulsion;

[0059] (3) slowly adding the sodium alginate solution to the emulsion, and adding a 15% mass concentration glacial acetic acid solution to adjust the pH to 3.5 to obtain a mixed solution;

[0060] (4) adding calcium chloride solution to the mixed solution, stirring and solidifying, standing, removing the supernatant, washing with distilled water, removing most of the solvent by vacuum rotary evaporation, filtering the precipitated solid, washing, and vacuum drying to obtain the gelatin-sodium alginate coated n-tetradecane phase change microcapsules;

[0061] The emulsifier is Tween-80, the mass ratio of n-tetradecane to the emulsifier is 1:0.2, the mass ratio of n-tetradecane, gelatin solution and sodium alginate solution is 1:1.5:2, the mass concentration of the sodium alginate solution in step (1) is 75%, the mass concentration of the gelatin solution is 75%, and the mass concentration of the calcium chloride solution in step (4) is 75%, and the amount of the calcium chloride solution added is 45wt% of the mixed solution.

[0062] The preparation method of the low temperature resistant polymer cement-based waterproof coating comprises the following steps:

[0063] S1, stirring the formulated amount of ethylene-vinyl acetate copolymer emulsion, water-based nitrile latex, film-forming aid, plasticizer, defoamer and deionized water at a speed of 6000 r / min for 3 hours, and then filling to obtain the A component;

[0064] S2. Put the formulated amount of silicate cement, magnesium phosphate cement, phase change microcapsules and sodium citrate into a powder mixing kettle, and stir at 80 r / min for 6 hours to obtain the B component.

[0065] Example 2

[0066] A low-temperature resistant polymer cement-based waterproof coating, the coating is composed of component A and component B; component A comprises the following raw materials in parts by weight: 100 parts of ethylene-vinyl acetate copolymer emulsion, 10 parts of water-based nitrile latex, 2 parts of film-forming aid, 3 parts of plasticizer, 1 part of defoamer and 20 parts of deionized water;

[0067] Component B includes the following raw materials in parts by weight: 100 parts of silicate cement, 50 parts of magnesium phosphate cement, 10 parts of phase change microcapsules, and 10 parts of sodium citrate;

[0068] Wherein, the film-forming aid is propylene glycol methyl ether acetate, the plasticizer is dioctyl adipate, and the defoamer is an organosilicon defoamer;

[0069] The preparation method of the phase change microcapsule comprises the following steps:

[0070] (1) adding sodium alginate and gelatin into distilled water respectively, stirring until dissolved, to obtain a sodium alginate solution and a gelatin solution;

[0071] (2) adding n-tetradecane and an emulsifier to the gelatin solution and mixing them uniformly to obtain an emulsion;

[0072] (3) slowly adding the sodium alginate solution to the emulsion, and adding a 10% mass concentration of glacial acetic acid solution to adjust the pH to 4.0 to obtain a mixed solution;

[0073] (4) adding calcium chloride solution to the mixed solution, stirring and solidifying, standing, removing the supernatant, washing with distilled water, removing most of the solvent by vacuum rotary evaporation, filtering the precipitated solid, washing, and vacuum drying to obtain the gelatin-sodium alginate coated n-tetradecane phase change microcapsules;

[0074] The emulsifier is Tween-80, the mass ratio of n-tetradecane to the emulsifier is 1:0.1, the mass ratio of n-tetradecane, gelatin solution and sodium alginate solution is 1:1:1, the mass concentration of the sodium alginate solution in step (1) is 70%, the mass concentration of the gelatin solution is 70%, and the mass concentration of the calcium chloride solution in step (4) is 70%, and the amount of the calcium chloride solution added is 40wt% of the mixed solution.

[0075] The preparation method of the low temperature resistant polymer cement-based waterproof coating comprises the following steps:

[0076] S1, stirring the formulated amount of ethylene-vinyl acetate copolymer emulsion, water-based nitrile latex, film-forming aid, plasticizer, defoamer and deionized water at a speed of 5000 r / min for 4 hours, and then filling to obtain the A component;

[0077] S2. Put the formulated amount of silicate cement, magnesium phosphate cement, phase change microcapsules and sodium citrate into a powder mixing kettle, and stir at 60 r / min for 8 hours to obtain the B component.

[0078] Example 3

[0079] A low-temperature resistant polymer cement-based waterproof coating, the coating consisting of component A and component B;

[0080] Component A includes the following raw materials in parts by weight: 150 parts of ethylene-vinyl acetate copolymer emulsion, 20 parts of water-based nitrile latex, 5 parts of film-forming aid, 5 parts of plasticizer, 3 parts of defoamer and 50 parts of deionized water;

[0081] Component B includes the following raw materials in parts by weight: 150 parts of Portland cement, 60 parts of magnesium phosphate cement, 20 parts of phase change microcapsules, and 20 parts of sodium citrate;

[0082] Wherein, the film-forming aid is propylene glycol methyl ether acetate, the plasticizer is dioctyl terephthalate, and the defoamer is an organosilicon defoamer;

[0083] The preparation method of the phase change microcapsule comprises the following steps:

[0084] (1) adding sodium alginate and gelatin into distilled water respectively, stirring until dissolved, to obtain a sodium alginate solution and a gelatin solution;

[0085] (2) adding n-tetradecane and an emulsifier to the gelatin solution and mixing them uniformly to obtain an emulsion;

[0086] (3) slowly adding the sodium alginate solution to the emulsion, and adding a glacial acetic acid solution with a mass concentration of 20% to adjust the pH to 3.0 to obtain a mixed solution;

[0087] (4) adding calcium chloride solution to the mixed solution, stirring and solidifying, standing, removing the supernatant, washing with distilled water, removing most of the solvent by vacuum rotary evaporation, filtering the precipitated solid, washing, and vacuum drying to obtain the gelatin-sodium alginate coated n-tetradecane phase change microcapsules;

[0088] The emulsifier is Tween-80, the mass ratio of n-tetradecane to the emulsifier is 1:0.3, the mass ratio of n-tetradecane, gelatin solution and sodium alginate solution is 1:2:2, the mass concentration of the sodium alginate solution in step (1) is 80%, the mass concentration of the gelatin solution is 80%, and in step (4), the mass concentration of the calcium chloride solution is 80%, and the amount of the sodium chloride solution added is 50wt% of the mixed solution.

[0089] The preparation method of the low temperature resistant polymer cement-based waterproof coating comprises the following steps:

[0090] S1, stirring the formulated amount of ethylene-vinyl acetate copolymer emulsion, water-based nitrile latex, film-forming aid, plasticizer, defoamer and deionized water at a speed of 8000 r / min for 2 hours, and then filling to obtain the A component;

[0091] S2. Put the formulated amount of silicate cement, magnesium phosphate cement, phase change microcapsules and sodium citrate into a powder mixing kettle, and stir at 100 r / min for 4 hours to obtain the B component.

[0092] Comparative Example 1

[0093] The difference between Comparative Example 1 and Example 1 is that: no phase change microcapsules are added, and equal amounts of gelatin, sodium alginate and n-tetradecane are directly added to component B.

[0094] Comparative Example 2

[0095] The difference between Comparative Example 2 and Example 1 is that gelatin-sodium alginate is not used to coat n-tetradecane, but gelatin-gum arabic is used to coat n-tetradecane. The specific preparation steps are as follows:

[0096] (1) Adding gum arabic and gelatin into distilled water respectively, stirring until dissolved, to obtain a gum arabic solution and a gelatin solution;

[0097] (2) adding n-tetradecane and an emulsifier to the gum arabic solution and mixing them uniformly to obtain an emulsion;

[0098] (3) slowly adding the gelatin solution to the emulsion, and adjusting the pH to 3.5 by adding a 15% glacial acetic acid solution to obtain a mixed solution;

[0099] (4) adding calcium chloride solution to the mixed solution, stirring and solidifying, standing, removing the supernatant, washing with distilled water, removing most of the solvent by vacuum rotary evaporation, filtering the precipitated solid, washing, and vacuum drying to obtain the gelatin-arabic gum coated n-tetradecane phase change microcapsules;

[0100] The emulsifier is Tween-80, the mass ratio of n-tetradecane to the emulsifier is 1:0.2, the mass ratio of n-tetradecane, gelatin solution and gum arabic solution is 1:1.5:2, the mass concentration of the sodium alginate solution in step (1) is 75%, the mass concentration of the gelatin solution is 75%, and the mass concentration of the calcium chloride solution in step (4) is 75%, and the amount of the calcium chloride solution added is 45wt% of the mixed solution.

[0101] Comparative Example 3

[0102] The difference between Comparative Example 3 and Example 1 is that instead of using gelatin-sodium alginate to coat n-tetradecane, sodium alginate-chitosan is used to coat n-tetradecane. The specific preparation steps are as follows:

[0103] (1) adding sodium alginate and chitosan into distilled water respectively, stirring until dissolved, to obtain sodium alginate solution and chitosan solution;

[0104] (2) adding n-tetradecane and an emulsifier to the sodium alginate solution and mixing them uniformly to obtain an emulsion;

[0105] (3) slowly adding chitosan solution to the emulsion, and adding 15% glacial acetic acid solution to adjust the pH to 3.5 to obtain a mixed solution;

[0106] (4) adding calcium chloride solution to the mixed solution, stirring and solidifying, standing, removing the supernatant, washing with distilled water, removing most of the solvent by vacuum rotary evaporation, filtering the precipitated solid, washing, and vacuum drying to obtain sodium alginate-chitosan coated n-tetradecane phase change microcapsules;

[0107] The emulsifier is Tween-80, the mass ratio of n-tetradecane to the emulsifier is 1:0.2, the mass ratio of n-tetradecane, chitosan and sodium alginate is 1:1.5:2, the mass concentration of the sodium alginate solution in step (1) is 75%, the mass concentration of the chitosan solution is 75%, and the mass concentration of the calcium chloride solution in step (4) is 75%, and the amount of the calcium chloride solution added is 45wt% of the mixed solution.

[0108] Comparative Example 4

[0109] The difference between Comparative Example 4 and Example 1 is that: in Comparative Example 4, magnesium phosphate cement is not added, and its reduced mass is distributed to the masses of silicate cement, phase change microcapsules, and sodium citrate according to the proportion of Example 1.

[0110] Comparative Example 5

[0111] The difference between Comparative Example 5 and Example 1 is that: in Comparative Example 5, no sodium citrate is added, and the reduced mass thereof is distributed to the masses of silicate cement, magnesium phosphate cement, and phase change microcapsules according to the proportion of Example 1.

[0112] Comparative Example 6

[0113] The difference between Comparative Example 6 and Example 1 is that: in Comparative Example 3, no silicate cement is added, and its reduced mass is distributed to the masses of magnesium phosphate cement, sodium citrate, and phase change microcapsules according to the proportion of Example 1.

[0114] Comparative Example 7

[0115] The difference between Comparative Example 7 and Example 1 is that: in Comparative Example 3, no phase change microcapsules are added, and the reduced mass is distributed to the masses of silicate cement, magnesium phosphate cement, and sodium citrate according to the proportion of Example 1.

[0116] Performance Testing

[0117] The polymer cement-based waterproof coatings obtained in Examples 1-3 and Comparative Examples 1-7 were mixed with component A and component B in a mass ratio of 1:1 and then roller-coated. The surface drying time and actual drying time at -5°C, tensile strength, elongation at break, bonding strength, low-temperature flexibility, freeze-thaw resistance and other performance indicators were tested with reference to GB / T23445-2009 "Polymer Cement Waterproof Coatings" and JC / T975-2005 "Waterproof Coatings for Roads and Bridges". See Table 1 for details.

[0118] Table 1 Performance test data of polymer cement-based waterproof coating

[0119]

[0120]

[0121] As shown in Table 1, Comparative Example 1 is to directly add gelatin, sodium alginate and n-tetradecane to the system, and the mechanical properties, low temperature resistance, alkali resistance and hydrophobicity of its waterproof coating are all worse than those of Example 1. This may be because the tiny size and uniform dispersion of the phase change microcapsules in Example 1 enable them to be more evenly distributed in the cement matrix, avoiding the agglomeration and uneven distribution that may occur when directly added. This uniform distribution helps to improve the mechanical properties and durability of cement-based materials. At the same time, in the form of microcapsules, n-tetradecane can stably exist in cement-based materials and play its role in heat storage and temperature regulation, thereby improving the low temperature resistance of cement materials.

[0122] In Comparative Example 2, the sodium alginate in the microcapsule material is replaced by gum arabic, and in Comparative Example 3, the gelatin in the microcapsule material is replaced by chitosan. The mechanical properties, low temperature resistance, alkali resistance and hydrophobicity of Comparative Examples 2 and 3 are all worse than those of Example 1. This may be because gelatin can form tiny pores in the cement paste to reduce the internal pressure generated by the expansion of water freezing, thereby reducing the formation of cracks and improving the low temperature resistance of the cement material. Sodium alginate can react with Mg in magnesium phosphate cement to form a small pore. 2+ A cross-linking reaction occurs to form a three-dimensional network structure to fill the pores in the polymer cement-based waterproof coating, thereby improving the density of the material, thereby reducing the space for water penetration and ice expansion at low temperatures, and enhancing the low temperature resistance of the material. Therefore, the present invention selects sodium alginate and gelatin as capsule materials, and the synergy of the two can effectively improve the mechanical properties and low temperature resistance of the material.

[0123] Comparative Examples 4-7 do not add silicate cement, magnesium phosphate cement, sodium citrate and phase change microcapsules respectively, and their performance is significantly lower than that of Example 1, indicating that silicate cement, magnesium phosphate cement, sodium citrate and phase change microcapsules may have a synergistic effect, which will produce a synergistic effect on the mechanical strength, water resistance and low temperature resistance of the waterproof coating.

[0124] In summary, the polymer cement-based waterproof coating of the present invention has the advantages of fast curing, good low-temperature flexibility, and strong freeze-thaw resistance.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A low temperature resistant polymer cement-based waterproof coating, characterized in that: The coating is composed of component A and component B; when used, component A and component B are mixed in a mass ratio of 1:(0.5-2); Component A comprises the following raw materials in parts by weight: 100-150 parts of ethylene-vinyl acetate copolymer emulsion, 10-20 parts of water-based nitrile latex, 2-5 parts of film-forming aid, 3-5 parts of plasticizer, 1-3 parts of defoamer and 20-50 parts of deionized water; Component B includes the following raw materials in parts by weight: 100-150 parts of silicate cement, 50-60 parts of magnesium phosphate cement, 10-20 parts of phase change microcapsules and 10-20 parts of sodium citrate; The wall material of the phase change microcapsule is a composite of gelatin and sodium alginate, and the core material is n-tetradecane.

2. The low temperature resistant polymer cement-based waterproof coating according to claim 1, characterized in that: The preparation method of the phase change microcapsule comprises the following steps: (1) adding sodium alginate and gelatin into distilled water respectively, stirring until dissolved, to obtain sodium alginate solution and gelatin solution; (2) adding n-tetradecane and an emulsifier to the gelatin solution and mixing them uniformly to obtain an emulsion; (3) slowly adding sodium alginate solution to the emulsion, adjusting the pH to 3.0-4.0, to obtain a mixed solution; (4) adding calcium chloride solution to the mixed solution, stirring and solidifying, standing, removing the supernatant, washing with distilled water, removing most of the solvent by vacuum rotary evaporation, filtering the precipitated solid, washing, and vacuum drying to obtain gelatin-sodium alginate coated n-tetradecane phase change microcapsules; The mass ratio of n-tetradecane to the emulsifier is 1:(0.1-0.3), and the mass ratio of n-tetradecane, gelatin solution and sodium alginate solution is 1:(1-2):(1-2).

3. The low temperature resistant polymer cement-based waterproof coating according to claim 2, characterized in that: The emulsifier is Tween-80.

4. The low temperature resistant polymer cement-based waterproof coating according to claim 2, characterized in that: In the step (3), a glacial acetic acid solution with a mass concentration of 10-20% is added to adjust the pH.

5. The low temperature resistant polymer cement-based waterproof coating according to claim 2, characterized in that: The mass concentration of the sodium alginate solution is 70-80%, the mass concentration of the gelatin solution is 70-80%, the mass concentration of the calcium chloride solution is 70-80%, and the amount of the calcium chloride solution added is 40-50wt% of the mixed solution.

6. The low temperature resistant polymer cement-based waterproof coating according to claim 1, characterized in that: The film-forming aid is propylene glycol methyl ether acetate; and / or the plasticizer is at least one of dioctyl sebacate, dioctyl adipate and dioctyl terephthalate; and / or the defoamer is a silicone defoamer.

7. The method for preparing the low-temperature resistant polymer cement-based waterproof coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, stirring and mixing the formulated amount of ethylene-vinyl acetate copolymer emulsion, water-based nitrile latex, film-forming aid, plasticizer, defoamer and deionized water, and filling to obtain the A component; S2. Put the formulated amount of silicate cement, magnesium phosphate cement, phase change microcapsules and sodium citrate into a powder mixing kettle, stir and mix to obtain the B component.

8. The method for preparing the low-temperature resistant polymer cement-based waterproof coating according to claim 7, characterized in that: In the step S1, the stirring speed is 5000-8000 r / min and the stirring time is 2-4 h.

9. The method for preparing the low-temperature resistant polymer cement-based waterproof coating according to claim 7, characterized in that: In step S2, the stirring speed is 60-100 r / min and the stirring time is 4-8 h.

10. Use of the low-temperature resistant polymer cement-based waterproof coating according to any one of claims 1 to 6 in the preparation of outdoor building coatings.

Citation Information

Patent Citations

  • Polymer cement RG waterproof coating

    CN103387359A